EL SÓCRATES JENOFONTEO COMO MAESTRO EMOCIONAL: LA ESFERA PÁšBLICA EN MEM. III.7. 1-9 DESDE UNA PERSPECTIVA ARENDTIANA (Stylos, 2021)
In Mem. III.7.1-9 Xenophon introduces a conversation held between the young Charmides and Socrates. The last one was trying to convince the first one to actively participate in the political affairs of the polis. The negative of Charmides was not rooted in a lack of capacities, since he had experience advising important Athenian officials in private meetings, but in the fact that he suffered from “shame” (Î±á¼°Î´ÏŽÏ‚) and “fear” (Ï†ÏŒÎ²Î¿Ï‚) of publicly showing himself to the mob.How can the emotional variation of Charmides in relation to the public space involved be explained? I consider that, if the philosophy of Hannah Arendt is incorporated to the interpretation of the previous passage, light can be shed over this question. Particularly in The Human Condition, she claimed that one of the main characteristics of Athenian democracy was the clear demarcation between the public and the private spheres of life. The polis had been capable of creating a “space of appearance” in which its citizens entered so as their actions and speeches there performed were kept in the collective memory. Furthermore, the public realm “was the only place where men could show who they really and inexchangeably were” (1998: 41).Therefore, Charmides emotions –the shame and fear of appearing in front of the mob– can be rooted in the fact a procedure took place in thar context which was totally absent in the private sphere: the construction of his civic identity as a citizen. What Charmides happened to do or say in the Assembly would become engraved in the collective memory of the polis.
Keywords: Xenophon – Arendt – public sphere – emotions.